Factors Affecting Job Satisfaction Mediated by Motivation in Employees of PT Port Hospital - Triambowo, Dicky; Berliyanti, Dita Oki; Nilasari, B. Medina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of Perceived Organizational Support and Internal Communication on Job Satisfaction with Motivation as a mediating variable in employees of PT. Port Hospital. The background of this research is based on the increasing job dissatisfaction in the health sector which has an impact on organizational performance and patient safety. A quantitative approach was used through a survey of 192 employees with standardized instruments and the Likert Scale. Data analysis was carried out using SPSS and SEM-AMOS. The results of the study show that Perceived Organizational Support and Internal Communication have a positive and significant effect on Job Satisfaction, both directly and through Motivation. These findings highlight the importance of organizational support and effective internal communication in increasing motivation and job satisfaction in a hospital setting.